A PPAR-gamma agonist protects from radiation-induced intestinal toxicity. Issue 2 (March 2017) - Mangoni, Monica; Sottili, Mariangela; Gerini, Chiara; Desideri, Isacco; Bastida, Cinzia; Pallotta, Stefania; Castiglione, Francesca; Bonomo, Pierluigi; Meattini, Icro; Greto, Daniela; Cappelli, Sabrina; Di Brina, Lucia; et al.
Objective: Because of its anti-inflammatory, anti-fibrotic, anti-apoptotic and anti-neoplastic properties, the PPAR-γ agonist rosiglitazone is an interesting drug for investigating for use in the prevention and treatment of radiation-induced intestinal damage. We aimed to evaluate the radioprotective effect of rosiglitazone in a murine model of acute intestinal damage, assessing whether radioprotection is selective for normal tissues or also occurs in tumour cells. Methods: Mice were total-body irradiated (12 Gy), with or without rosiglitazone (5 mg/kg/day). After 24 and 72 hours, mice were sacrificed and the jejunum was collected. HT-29 human colon cancer cells were irradiated with a single dose of 2 (1000 cells), 4 (1500 cells) or 6 (2000 cells) Gy, with or without adding rosiglitazone (20 µM) 1 hour before irradiation. HT-29-xenografted CD1 mice were irradiated (16 Gy) with or without rosiglitazone; tumour volumes were measured for 33 days. Results: Rosiglitazone markedly reduced histological signs of altered bowel structures, that is, villi shortening, submucosal thickening, necrotic changes in crypts, oedema, apoptosis, and inflammatory infiltrate induced by irradiation. Rosiglitazone significantly decreased p-NF-kB p65 phosphorylation and TGFβ protein expression at 24 and 72 hours post-irradiation and significantly decreased gene expression of Collagen1, Mmp13, Tnfα and Bax at 24 hours and p53 at 72 hours post-irradiation. Rosiglitazone reduced HT-29 clonogenic survival, but only produced a slight reduction of xenograft tumour growth. Conclusion: Rosiglitazone exerts a protective effect on normal tissues and reduces alterations in bowel structures and inflammation in a radiation-induced bowel toxicity model, without interfering with the radiation effect on HT-29 cancer cells. PPAR-γ agonists should be further investigated for their application in abdominal and pelvic irradiation.